Kritik Feminisme Pada Web Series “Gadis Kretek” - Jaya, Eko Pebryan; Yogsunandar, Harry (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
Technological developments and transformations in the entertainment industry have brought about major changes in the way we access and consume films. Currently, films are not only available in cinemas, but have also spread through online streaming services. Various series with various story themes appeared, one of which was